2022
DOI: 10.1021/acsestwater.2c00066
|View full text |Cite
|
Sign up to set email alerts
|

Difference and Network Analysis of Functional Genes Revealed the Hot Area of Carbon Degradation, Nitrogen, Phosphorus, and Sulfur Cycling in Blending Systems with Pyrite and Poly(3-hydroxybutyrate-hydroxyvalerate) for Nitrogen and Phosphorus Removal

Abstract: A higher denitrification rate was realized via controlling the mass ratio of pyrite and poly(3-hydroxybutyrate-hydroxyvalerate) (PHBV) under natural aerobic conditions. The results showed that the suitable mass ratio of PHBV and pyrite could be 1:2 with its removal efficiency of nitrogen and phosphorus of 99.7 and 53.4%, respectively. The PHBV/pyrite system has formed the spatial patterns of the biofilm community, such as Dechloromons attached to the pyrite surface, Rhodocyclaceae attached to the PHBV surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These authors reported the coexistence of autotrophic denitrifiers such as Thiobacillus (20.3%) and heterotrophic denitrifiers such as Anaerolineaceae (6.0%). We previously reported that Thiobacillus and Acidovorax were enriched on pyrite and poly-3-hydroxybutyrate-hydroxyvalerate (PHBV) surfaces, respectively, in a simple blend of pyrite and PHBV in a mixotrophic denitrification system. , However, pyrite is too large to give full play to the potential of pyrite-based autotrophic denitrification in the above-mentioned pyrite-based mixotrophic denitrification systems, and pyrite is chemically oxidized by direct exposure to air, leading to massive consumption of pyrite and high sulfate accumulation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors reported the coexistence of autotrophic denitrifiers such as Thiobacillus (20.3%) and heterotrophic denitrifiers such as Anaerolineaceae (6.0%). We previously reported that Thiobacillus and Acidovorax were enriched on pyrite and poly-3-hydroxybutyrate-hydroxyvalerate (PHBV) surfaces, respectively, in a simple blend of pyrite and PHBV in a mixotrophic denitrification system. , However, pyrite is too large to give full play to the potential of pyrite-based autotrophic denitrification in the above-mentioned pyrite-based mixotrophic denitrification systems, and pyrite is chemically oxidized by direct exposure to air, leading to massive consumption of pyrite and high sulfate accumulation …”
Section: Introductionmentioning
confidence: 99%
“…Tight microbial interactions between autotrophs and heterotrophs in the mixotrophic denitrification system help to improve the system’s stability and thus optimize nitrogen removal performance . Among mixotrophic denitrification systems, pyrite-based mixotrophic denitrification has gained the most research attention, which relies on coupling sulfur-based autotrophic denitrifying bacteria with heterotrophic denitrifying bacteria. , For instance, Jin et al constructed a simple blend of pyrite and sawdust to form a mixotrophic denitrification system, which achieved high NO 3 – –N removal rates of 19.3 ± 1.8 g N/m 3 /d. These authors reported the coexistence of autotrophic denitrifiers such as Thiobacillus (20.3%) and heterotrophic denitrifiers such as Anaerolineaceae (6.0%).…”
Section: Introductionmentioning
confidence: 99%